No evidence to support CTLA-4 as a susceptibility gene in MS families: the Canadian Collaborative Study. - Dyment, D; Steckley, J; Willer, C; Armstrong, H; Sadovnick, A; Risch, N; Ebers, G (2002)
Two polymorphisms of the CTLA-4 gene were genotyped in 232 sibling pairs affected with multiple sclerosis (MS) from 185 families. The CTLA-4 polymorphisms genotyped were a 3' untranslated (AT)(n) microsatellite and an alanine/threonine RFLP of exon 1. There was no evidence observed for linkage by either identity-by-descent (ibd) or identity-by-state (ibs) methods. A transmission disequilibrium test (TDT) was performed and no preferential transmission of alleles was observed. Upon stratification of patients, there was no preferential transmission observed based upon gender, by presence or absence of HLA*DRB1*15, by ethnicity or by clinical course of the disease. CTLA-4 does not appear to be a major MS susceptibility locus in Canadian multiplex families.